A Novel Methodology for Providing Security in Electronic Health Record Using Fuzzy Based Multi Agent System - Alanezi, Mohammed Ateeq (International Journal of Online and Biomedical Engineering (iJOE), 2021)
Privacy and security are crucial when it comes to the implementation of Electronic Healthcare Records (HER). Whenever a patient visits a doctor, their health records are updated since it consists of vital information on the patient's health and well-being. It also comprises of description about the previous and current treatment quality.Multi-Agent Systems can support E-Healthcare applications for improving quality of life. The availability and use of extensive systems for EHR has increased dramatically. The EHR technology currently available consists of health information of various patients which helps those people to monitor their health. These information should be protected from being altered or mishandled. Various studies have been conducted in the past literature to improve the protection and privacy requirements in E-health services. Despite this, it hasn't been entirely improved. This article proposes a Fuzzy based multi-agent system architecture that uses agents and fuzzy logic to monitor the flow and access of the EHR record using fuzzy logic and multi agents. Architecture comprises of multi agent and fuzzy systems are proposed. In this system, we have employed Action/ Computation (Interface) agent, communication interface agent and verification agent and Communication Module Agent. These agents collaboratively worked one another in order to obtain the desired output. These agent based e-health system can increase the accuracy of data transfer by providing additional security in selecting the user who handles the data. It also monitors the communication between different medical units in the health system.